Menopausal Women: A Survey to Create a Geographic Information System of Medicinal Plants Used in Folk Remedies in Chanthaburi Province - sinwat, Suratsawadee (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Traditional Thai medicine and local health wisdom play a vital role in Thai society, particularly in caring for menopausal women experiencing hormonal changes. This treatment focuses on the use of local herbs, reflecting knowledge and experiences passed down through generations to alleviate related symptoms such as hot flashes and mood swings. Currently, support for the use of herbs in healthcare is growing, leading to a continuous increase in the herbal product market. This research aims to study treatment methods for menopausal patients using traditional Thai medicine, explore herbs used by local healers in Chanthaburi Province, and create a Geographic Information System (GIS) of these herbal plants. The use of GIS aids in collecting spatial data regarding the herbs used to treat menopausal patients, allowing for the analysis of the distribution of herbal plants and the geographical factors affecting their growth. Methodology: A mixed research method was employed, involving the study of treatment methods and the use of herbs through interviews and observations, as well as the creation of GIS to identify the locations of herbs used in treatment. Data quality was verified using triangulation to ensure reliable information, which is effective in promoting local wisdom regarding traditional Thai medicine within communities. Results: It was found that local healers utilize various herbs with properties that nourish the blood and balance the body's elements, such as red sandalwood, long pepper, black pepper, cardamom, and turmeric. Treating menopausal symptoms requires careful communication and follow-up on treatment outcomes to help patients understand the duration and importance of ongoing care. Furthermore, preserving local wisdom related to herbs is crucial for promoting health and improving the quality of life for menopausal women. The use of GIS in analyzing herbal plant data helps create effective distribution maps, including assessing the impacts of climate change. Conclusion: This allows for the sustainable conservation and utilization of herbal resources. Integrating GIS data with local wisdom will enhance the effectiveness of treating menopausal women. In the future, this will lead to the development of health policies that sustainably and appropriately respond to community needs.